Pengaruh Inovasi dan Orientasi Kewirausahaan Terhadap Kinerja Usaha yang di Mediasi oleh Perilaku Kewirausahaan Pada UMKM Kota Kendari - Rachmat Rialdy Hasan; Hasan Aedy; Rachmi Hariaty Hasan; Reski Auliany Hasan; Dzulfikri Azis Muthalib (STIE ENAM ENAM KENDARI, 2025)
The purpose of this study is to explore the influence of innovation and entrepreneurial orientation on entrepreneurial behavior and business performance. More specifically, it aims to examine and explain the mediating role of entrepreneurial behavior. This study employs an explanatory research design, and data were collected using a survey method. The sampling technique used was purposive sampling, with a total sample of 97 small and medium enterprises located in Kendari City. The respondents selected as samples were business owners. The analytical method used for hypothesis testing was Partial Least Squares (PLS). The results indicate that innovation has a negative and significant effect on business performance but a positive and significant effect on entrepreneurial behavior. Entrepreneurial orientation has a positive and significant effect on both entrepreneurial behavior and business performance. Entrepreneurial behavior also has a positive and significant effect on business performance. Furthermore, entrepreneurial behavior serves as a mediating variable in therelationship between innovation and business performance. Finally, entrepreneurial behavior also mediates the relationship between entrepreneurial orientation and business performance.